Cost effectiveness analysis of ceftriaxone with cefoperazon in thypoid patients at X Mataram Hospital - Khairani, Sondang; Manninda, Reise; Widodo, Akhmad Fajri; Raharjo, Lalu Joko (Faculty of Pharmacy, Universitas Pancasila, 2024)
Typhoid is the third most common cause of hospitalisation in Indonesia, affecting 100,000 people every year. Typhoid fever, with an average case fatality rate of 2.45% at X Mataram Hospital, was among the top 10 most common inpatient illnesses in 2019 and 2020. Antibiotics are effective in reducing typhoid infection, lowering body temperature, shortening the length of hospitalisation, and reducing mortality. The aim study to determine the cost-effectiveness of using ceftriaxone and cefoperazone antibiotics for typhoid patients at X Mataram Hospital. Method a compares two groups of antibiotics and evaluates direct costs and clinical outcomes clinic (length of stay and time free of fever). This research is using ACER's cost-effectiveness analysis. The study included 63 samples with an average direct cost of Rp 3,645,106 for cefoperazon and Rp 3,168,106 for ceftriaxone. According to the ACER analysis results, hospitalisation with ceftriaxone is more cost-effective a lower cost of Rp 704,023 and based on fever-free time, cefoperazone is more cost-effective at Rp. 1,024,094. No correlation between antibiotic effectiveness and fever-free time, no correlation between antibiotic effectiveness and length of hospitalisation (p-value >0.05).